Pendampingan Materi Muatan Lokal di SDN 193 Pekanbaru - Elpri Darta Putra; Mitha Dwi Anggriani (Pucuk Rebung: Jurnal Pengabdian kepada Masyarakat, 2021)
This service aims to improve the ability to master local content in elementary schools and to actualize and develop local content materials in elementary schools. The implementation of this community service was motivated by a request for teachers of SD Negeri 193 in Marpoyan Damai District, Pekanbaru City, who had difficulty in actualizing local content material. This service activity was carried out in December 2019, carried out in 2 stages, namely: (1) in this first stage community service activities include mentoring local content material, where at this stage participants get material related to local content and material examples local content; and (2) the second stage, community service activities are carried out by means of the teacher making presentations and continued with discussions and providing input that involves all training participants. The results of the activities during the implementation of mulok material mentoring for teachers at SDN 193 Pekanbaru showed the enthusiasm of the participants with the various questions raised by the participants.